Humans in the Cyber Loop: Perspectives on Social Cybersecurity - Domalewska, Dorota; Gasztold, Aleksandra; Wrońska, Agnieszka (Studies in Critical Social Sciences, 2025)
Humans in the Cyber Loop: Perspectives on Social Cybersecurity addresses the evolving role of humans in cyberspace through an analysis of how digital interactions and advancements both shape and are shaped by societal, economic, and political factors. The book systematically explores social cybersecurity, the impact of disinformation on democratic processes, the influence of social media on public opinion, and the implications of algorithmic decision-making to demonstrate the importance of building societal resilience to cyber attacks and to better understand specific needs and challenges in this domain.